INTEGRATED CIRC TECHNIQUE, AUTHENTIC MATERIALS, AND ONLINE LEARNING DURING COVID-19 - Suharti Sirajuddin; Muhammad Yahrif; Muh Indra Budiman (Journal of English Educational Study (JEES), 2022)
This research aimed at finding out the integration of CIRC technique, authentic materials, and online learning during the Covid-19 pandemic, to enhance students writing ability, especially for procedure text. The objective of the research was junior high school class IX in Gowa South Sulawesi, which had 40 students. In this study, researchers used mix method namely explanatory research (quantitative and qualitative method). For quantitative analysis, researchers applied experimentally group by using pre and post-test. For qualitative analysis, the participants had to answers an open-ended questionnaire related to their perspective of the treatment session. The result of the quantitative data analysis showed that the percentage of students' results post-test was higher than pre-Test, which achieved 97.5 % in post-test. The result of the t-test value showed that the combination of CIRC technique, authentic materials, and online learning, affected positively students writing ability, and it was in line with students’ perception of the application of CIRC technique and authentic material. However, from the results of qualitative data, some students preferred to study in class and interact directly with teachers and friends, and some students showed a lack of motivation to cooperate.